2011
DOI: 10.1039/c1ee01541a
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of carbon and nitrogen in the products from hydrothermal liquefaction of low-lipid microalgae

Abstract: Microalgae are considered to be a promising alternative feedstock for next generation biofuels because of their rapid photosynthetic growth rates and less impact on land-use for food production compared with grain and other lignocellulosic biomass. In this study, a fast-growing, low-lipid, high-protein microalga species, Chlorella pyrenoidosa, was converted via hydrothermal liquefaction (HTL) into four products: bio-crude oil, aqueous product, gaseous product, and solid residue. The effects of operating condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(173 citation statements)
references
References 43 publications
8
161
2
2
Order By: Relevance
“…Hydrothermal liquefaction (HTL) is a thermal process that converts biomass to several products including an oil portion with high heating value (Alba et al 2012;Biller and Ross 2011;Brown et al 2010;Duan and Savage 2011;Minowa et al 1995;Vardon et al 2011;Yu et al 2011). HTL offers several advantages compared to other approaches.…”
Section: Context and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrothermal liquefaction (HTL) is a thermal process that converts biomass to several products including an oil portion with high heating value (Alba et al 2012;Biller and Ross 2011;Brown et al 2010;Duan and Savage 2011;Minowa et al 1995;Vardon et al 2011;Yu et al 2011). HTL offers several advantages compared to other approaches.…”
Section: Context and Motivationmentioning
confidence: 99%
“…The HTL yield is defined here to be the mass of HTL oil recovered per dry mass of algae processed, sometimes written as a percentage. Numerous studies are reported in the literature and each reports different yields for the various fractions (Table 1) and different distributions of solids between oil and aqueous phases (Alba et al 2012;Biller and Ross 2011;Brown et al 2010;Duan and Savage 2011;Minowa et al 1995;Valdez et al 2011;Vardon et al 2011;Yu et al 2011). The product distribution may be influenced by many factors, including chemical composition of the algae, reaction temperature, retention time, feedstock solid content, and catalyst usage.…”
Section: Hydrothermal Liquefaction Processmentioning
confidence: 99%
See 2 more Smart Citations
“…High-lipid microalgae mean a lipid accumulation in microalgae under a stressed condition such as nitrogen depletion. It will sacrifice biomass productivity, reduce the net energy yield, and make the process very sensitive to contamination (Yu et al, 2011). According to Williams and Laurens (2010), high lipid containing algae may not necessarily be the most favorable candidate organisms.…”
Section: Introductionmentioning
confidence: 99%